Should treatment of low-level rifampicin mono-resistant tuberculosis be different?. (May 2021) - Gopie, F.A.; Commiesie, E.; Baldi, S.; Kamst, M.; Kaur, D.; de Lange, W.C.M.; Pinas, P.S.; Stijnberg, D.; Wongsokarijo, M.; Zijlmans, C.W.R.; de Zwaan, R.; van Soolingen, D.; et al.
Abstract: Background: Rifampicin resistant tuberculosis (RR-TB) was frequently detected in Suriname after the introduction of Xpert MTB/RIF in 2012. Subsequent phenotypic drug-susceptibility testing (DST) was not conclusive at that moment, while RR-TB patients treated with first-line tuberculostatics had good treatment outcome. In our study, we analysed this interesting observation. Methods: We collected demographic and clinical characteristics and treatment outcome of TB patients from May 2012-December 2018 and performed a univariate and multivariate analysis to assess possible associations with resistance to rifampicin. Secondly, we conducted whole genome sequencing on all available Mycobacterium tuberculosis isolates that had a rifampicin resistance in the Xpert MTB/RIF test and performed phenotypic DST on selected isolates. Findings: RR-TB was detected in 59 (9.6%) patients confirmed by Xpert. These patients were treated with rifampicin-containing regimens in most (88%) of the cases. In all 32 samples examined, a D435Y mutation in the rpoB gene was identified; only one isolate revealed an additional isoniazid mutation. Phenotypic DST indicated low-level rifampicin resistance. In multivariate analysis, the Creole ethnicity was a factor associated with rifampicin resistance (aOR 3.5; 95%CI 1.9–6.4). The treatment success rate for patients with RR-TB (78.0%) was comparable to the treatment outcome in non-RR-TB patients 77.8%. Interpretation: This study confirms a low-level rifampicin mono-resistance in TB patients of Suriname. These patients could benefit from a first-line regimen with high dose rifampicin (or rifabutin), rather than from the lengthy treatment regimens for rifampicin-resistant and multi-drug resistant TB, a concept of stratified medicine also advocated for the treatment of TB. Funding: None.